Developing a system for comprehensive regional Eco-environmental quality assessment in mountainous areas—A case study of Western Sichuan, China - Chen, Xiaojie; Chen, Shengbin; He, Zhengwei; Xue, Dongjian; Fang, Guozheng; Pan, Kaiwen; Fang, Kun (Frontiers in Environmental Science, 2022)
Eco-Environmental quality assessment is an important process for regional sustainable development, and is conducive for promoting the construction of ecological civilization. It is also the basis of digital management and decision-making for ecological environment in the near future. Due to the particularity of mountainous areas, its Eco-environmental quality assessment needs to be deeply studied. To scientifically analyze and evaluate the Eco-environmental quality in mountainous Western Sichuan in 2019 at township (street) units, the AHP-Entropy model was developed and constructed, based on the indicators representing biological richness, vegetation cover, water network density, land stress, and social-economic stress. The developed model has more complete assessment indicators system, easier data acquisition and higher accuracy. The Eco-environmental indicators representing Eco-environmental quality can be divided into five levels: Better, Good, Moderate, Bad and Worse. The results show that: (1) the Eco-environment in the study area is generally Good, and the distribution of better and Bad is less. (2) The areas with better ecological environment are mainly distributed in Longmen Mountain, Daliang mountain and Qionglai mountain. The areas with worse ecological environment quality are mainly distributed in the west of Chengdu Plain, Panzhihua urban area, and Shaluli mountain. (3) The areas with better ecological environment quality are due to high vegetation coverage, high habitat quality, and low degree of land degradation such as land desertification and soil erosion. The areas with moderate Eco-environmental quality are mainly caused by frequent human activities or serious land degradation. The comprehensive regional Eco-environmental quality assessment system constructed in this paper can also be used in other mountainous areas.